Managing Organizational Culture for Effective Internal Control From Practice to Theory - Pfister, Jan A. (Contributions to Management Science, 2009)
In times of economic and financial crises, the content of this book rings true. While we often look at formal compliance procedures, incentive systems and other 'technical' ways to ensure effective internal control, this study emphasizes a different perspective: How do the management principles and practices influence organizational culture in order to enhance control effectiveness? New theory is provided on the way that tone at the top - leadership, sustainability, accountability, and other social control aspects - is combined with formal control. The research is based on in-depth interviews with senior-level people (e.g. executives, managers, auditors) from more than 18 renowned U.S. and Swiss companies, and theory from fields of sociology and social psychology. In contrast to contemporary accounting and control research, where culture provides a context for control, here any control mechanism can in turn influence culture. The study offers innovative insights for both academics and practitioners including: a) a new research framework for analyzing the links between culture and control; b) statements from senior-level people of eBay, Google, Hewlett Packard, Intel, Levi Strauss & Co., Microsoft, Motorola, Novartis and many more; c) a practice-oriented tool to proactively mitigate typical roots of internal control failures; d) integrated theory on social systems, personal and organizational values and organizational corruption; e) a foreword from Solomon N. Darwin, University of California at Berkeley.